Pengelolaan Aplikasi Rencana Kegiatan Dan Anggaran Sekolah Di Smp Negeri 5 Bengalon - azmia azmia; Mahfud Ifendi; Muhammad Imam Syafi’i (Manajemen Pendidikan Program Doktor, 2026)
The management of the School Activity Plan and Budget (RKAS) application at SMP Negeri 5 Bengalon is a process that undergoes continuous improvement and updating each year. Consequently, this study aims to examine the management of the RKAS application, identify supporting and inhibiting factors, and determine solutions to ensure school operations remain uninterrupted. This is a field study employing a descriptive qualitative approach, with informants including the School Principal, the Treasurer, and the RKAS Operator. Data collection techniques involved observation, interviews, and documentation. The results indicate that the management of the RKAS application encompasses planning, budget formulation, administration, implementation, budget disbursement, and accountability reporting. Supporting factors include hardware facilities (laptops), network infrastructure (Starlink), and early data validation. However, there are also obstacles, specifically the limited range of item descriptions available in the system compared to actual needs in the field. To safeguard internal school operations, the study proposes tactical solutions such as establishing priority scales, maintaining responsive team communication, and swiftly utilizing budget reallocation mechanisms. Externally, an early verification mechanism by the Education Office serves as a crucial preventive measure for the early detection of reporting errors.